Amorphous-crystal bimetallic catalyst, its preparation method and application
By preparing amorphous-crystalline bimetallic catalysts, the problems of activity and stability of copper-iron catalysts were solved. A cross-linked structure of long-range disordered amorphous matrix and local microcrystalline domains was constructed, which improved catalytic activity and stability and achieved high-efficiency catalytic degradation performance.
Patent Information
- Application Number
- CN202611072533.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-07-20
AI Technical Summary
Existing copper-iron bimetallic catalysts suffer from dual bottlenecks in activity and stability. Long-range ordered highly crystalline materials lack active sites on their surface and are prone to thermal passivation, while long-range disordered amorphous materials are prone to structural reorganization under high-energy surface stress, making it difficult to meet industrial requirements.
Amorphous primary products were prepared by stirring under the spatial confinement of surfactants and adding a weak base agent to carry out a co-precipitation reaction. The products were then calcined at 250~400℃ for 0.5~1.5h to construct an amorphous-crystalline bimetallic catalyst, forming a structure in which a long-range disordered amorphous matrix and locally distorted microcrystalline domains are cross-linked.
It significantly enhances the redox cycle kinetics between bimetallic multivalent states, improves catalytic activity, reduces local intrinsic resistance, achieves highly efficient catalytic degradation performance, and avoids the risks of thermal passivation and secondary poisoning.
Smart Images

Figure CN122582991B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, specifically to an amorphous-crystalline bimetallic catalyst, its preparation method, and its application. Background Technology
[0002] In recent years, heterogeneous advanced oxidation processes (AOPs) based on persulfate (PMS) have shown great promise in the removal of antibiotic-resistant organic pollutants from wastewater due to the strong oxidizing reactive oxygen species they generate. Among numerous catalytic materials, copper-iron (Cu-Fe) based bimetallic materials stand out due to their abundant reserves, low cost, and bimetallic multivalent states (Cu... 2+ / Cu + with Fe 3+ / Fe 2+ The strong synergistic effect of electron cycling has become a research hotspot for heterogeneous activated PMS.
[0003] However, existing copper-iron bimetallic catalysts face dual bottlenecks in activity and stability. Traditionally prepared copper-iron catalysts typically exhibit a long-range ordered, highly crystalline state with a tight internal lattice, high energy barriers, and an extreme lack of coordinatingly unsaturated active sites and defects on the surface. This results in slow macroscopic reaction kinetics and widespread thermal passivation of catalytic activity. Conversely, while long-range disordered amorphous materials contain a high density of metastable active sites due to severely distorted chemical bonds, as thermodynamically unstable phases, they are prone to spontaneous structural reorganization and framework thermal collapse during conventional washing and drying processes or actual catalytic reactions due to high capillary forces and high-energy surface stresses. Furthermore, due to their long-range disordered internal network, they typically possess high local intrinsic resistance, and their self-limiting low electron migration efficiency easily hinders the flow kinetics of bimetallic multivalent state cycles, making it difficult to meet the industrial requirements for long-term cyclic use. Summary of the Invention
[0004] The technical problem to be solved by this invention is how to overcome the defects of crystalline or amorphous bimetallic catalysts and improve the catalytic activity of bimetallic catalysts.
[0005] The present invention solves the above-mentioned technical problems through the following technical means:
[0006] The first aspect of this invention provides a method for preparing an amorphous-crystalline bimetallic catalyst, comprising the following steps: S1. Iron salt, copper salt and hypophosphite are dissolved in water and a surfactant is added to obtain a mixture. A weak alkali is added to the mixture under stirring, the pH is adjusted and a co-precipitation reaction is carried out. After the reaction is completed, the mixture is sealed and aged, and solid-liquid separation is performed to obtain an amorphous initial product. S2. The amorphous primary product is ultrasonically eluted, centrifuged, sealed and aged, and vacuum dried to obtain a precursor; the precursor is calcined at 250~400℃ for 0.5~1.5h to obtain an amorphous-crystalline bimetallic catalyst.
[0007] Beneficial effects: The catalyst of the present invention is rapidly nucleated by co-precipitation reaction after stirring under the spatial confinement of surfactant and adding weak base agent to prepare amorphous primary product. Then, it is calcined at 250~400℃ for 0.5~1.5h to capture and fix an amorphous-crystalline bimetallic catalyst in situ inside the material, which is a cross-linked symbiosis of long-range disordered amorphous parent material and locally distorted microcrystalline domains.
[0008] The bimetallic catalyst retains the structure of the amorphous matrix rich in high-density defects while the locally precipitated distorted microcrystalline domains act as conductive network nodes, effectively reducing the excessively high local intrinsic resistance within the amorphous material and constructing a rapid inorganic electron transport channel. This phase synergy effect of the biphase structure significantly enhances the redox cycle kinetics between the multiple valence states of the bimetallic catalyst, improving its excellent heterogeneous oxidation catalytic activity in activating persulfate.
[0009] Preferably, the stirring speed is 700~900 rpm.
[0010] Preferably, the iron salt includes at least one of ferric chloride, ferric sulfate, ferric nitrate, or ferrous ammonium sulfate.
[0011] Preferably, the copper salt includes at least one of copper chloride, copper sulfate, copper nitrate, or copper acetate.
[0012] More preferably, the iron salt is ferric nitrate; the copper salt is copper nitrate.
[0013] Beneficial effects: The use of nitrates in this invention ensures that anions are completely converted into gaseous substances during calcination, avoiding residual poisoning of catalytic sites.
[0014] Preferably, the molar ratio of iron to copper in iron salts and copper salts is 1:1 to 3.
[0015] Preferably, the molar ratio of the sum of iron and copper in the iron salt and copper salt to phosphorus in the hypophosphite is 20~100:1.
[0016] Preferably, the surfactant includes at least one of bis(dodecyl dimethyl)ammonium bromide, hexadecyl trimethylammonium bromide, or sodium dodecylbenzenesulfonate.
[0017] Beneficial effects: This invention constructs a nano-confined microreactor using surfactants with large steric hindrance and long chains, which forcibly blocks the long-range ordered growth of crystal nuclei. This is the key to the institutionalization of perfectly locking the initial reactants in a long-range disordered amorphous state.
[0018] Preferably, the mass-volume ratio of surfactant in the mixture is 0.25~0.5 g / L.
[0019] Preferably, the weak alkaline agent includes at least one of ammonium bicarbonate, sodium bicarbonate or urea, with a pH of 7.5 to 9.5.
[0020] More preferably, the weak base agent is ammonium bicarbonate.
[0021] Beneficial effects: This invention uses ammonium bicarbonate as a weak alkali agent, whose decomposition products are gases with weak complexing properties, enabling instantaneous homogeneous nucleation of bimetallic ions.
[0022] Preferably, the coprecipitation reaction time is 20-40 min.
[0023] Preferably, the temperature for sealed aging is 0~5℃ and the time is 2~6h.
[0024] Preferably, the amorphous primary product is introduced into water at 50°C for ultrasonic elution.
[0025] Preferably, the ultrasonic elution power is 100~200W and the time is 5~10min.
[0026] Preferably, the vacuum drying temperature is 55~65℃ and the time is 12~24h.
[0027] The second aspect of the present invention provides a method for preparing the above-mentioned amorphous-crystalline bimetallic catalyst to obtain the amorphous-crystalline bimetallic catalyst.
[0028] The third aspect of this invention provides the application of the above-mentioned amorphous-crystalline bimetallic catalyst in the catalytic degradation of organic pollutants in water.
[0029] Preferably, an amorphous-crystalline bimetallic catalyst is added to water, and persulfate is added as an oxidant to activate and degrade the organic pollutants.
[0030] Preferably, the amount of amorphous-crystalline bimetallic catalyst added is 0.1~0.2 g / L.
[0031] Preferably, the concentration of persulfate is 0.1~0.3 mmol / L.
[0032] Preferably, the organic pollutant is tetracycline.
[0033] Compared with existing technologies, the present invention has the following advantages: 1. A qualitative leap in catalytic degradation performance: This invention achieves a dramatic catalytic degradation kinetic in the application of activated persulfate for the degradation of tetracycline by calcining the precursor at 250-400℃ for 0.5-1.5 h. Experimental results show that the amorphous-crystalline bimetallic catalyst prepared in this invention exhibits a sharp drop in C / C ratio to 0.3477 within only 5 min of reaction, and completes removal within 30 min (with a residual rate of only 0.0102). The degradation curve is extremely low overall, and its removal efficiency is not only significantly better than that of the untreated amorphous control group, but also completely widens the performance gradient with the fully crystalline thermally passivated control group.
[0034] 2. Constructing a heterogeneous interface to accelerate electron internal circulation: A catalyst was precisely controlled through thermal treatment, successfully enabling the synergistic coexistence of a high-defect amorphous substrate and locally distorted microcrystalline domains. This structure effectively overcomes the bottleneck of low self-limiting electron migration efficiency in amorphous materials, utilizing the conductive network node effect of the microcrystalline domains to greatly accelerate the Cu in the system. 2+ / Cu + and Fe 3+ / Fe 2+ The electron transfer cycle efficiency of the redox pair endows the catalyst with ultra-high catalytic activity at the microscopic level, which is a departure from conventional fully crystalline materials.
[0035] 3. Precisely avoids thermal passivation and effectively preserves the active site reservoir: This invention clarifies the crucial role of time regulation in the evolution of the amorphous framework. By controlling the calcination time at the critical point, both the inorganicization of precursor components and stress release are achieved, while perfectly avoiding the large-area thermal collapse and defect recombination repair (thermal passivation) of the high-energy disordered amorphous substrate caused by long-term thermal driving, thus maximizing the preservation of the surface's coordination-unsaturated active sites.
[0036] 4. Green and efficient, with no risk of secondary poisoning: The entire process uses nitrates and ammonium bicarbonate, which can be completely converted into gaseous substances, as raw materials. Combined with a unique gradient thermal washing process, macromolecular surfactants are completely removed, ensuring a high degree of cleanliness on the catalyst surface. This eliminates the problem of catalytic site poisoning caused by residual impurity ions in conventional preparation, and has extremely high industrial application and environmental protection value. Attached Figure Description
[0037] Figure 1 This is a microscopic image of the amorphous-crystalline bimetallic catalyst in Example 1 of the present invention; Figure 2 These are the XRD patterns of the bimetallic catalysts in Example 1, Comparative Example 1, and Comparative Example 2 of this invention; Figure 3 These are graphs showing the degradation of tetracycline by the bimetallic catalyst in Examples 1, 1, and 2 of this invention. Figure 4These are the degradation curves of tetracycline by the amorphous-crystalline bimetallic catalyst in Examples 1-7 of this invention; Figure 5 These are the graphs showing the degradation of tetracycline by the metal catalyst in Example 1 and Comparative Examples 1-5 of this invention. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0040] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0041] This invention provides a method for preparing an amorphous-crystalline bimetallic catalyst, specifically comprising the following steps: S1. Iron salt, copper salt, and hypophosphite are dissolved in water and continuously magnetically stirred until completely dissolved. The molar ratio of iron to copper in the iron and copper salts is 1:1~3. This constructs a highly distorted local atomic coordination structure in the amorphous framework from the source, which is the microscopic core for later in-situ construction of a two-phase coexistence state and the construction of local structural asymmetry. The introduction of hypophosphite not only significantly improves the crystallization activation energy barrier of the precursor by utilizing the difference in heterogeneous atomic radii. The molar ratio of the sum of iron and copper in the iron and copper salts to phosphorus in the hypophosphite is 20~100:1, obtaining a homogeneous salt solution. A surfactant is added to the salt solution and stirred evenly to construct a mixed solution with spatial topological confinement effect. The mass-volume ratio of surfactant in the mixed solution is 0.25~0.5 g / L. A weak alkali agent is rapidly added to the mixed solution at 700~900 rpm to adjust the pH to 7.5~9.5. This rapid one-time pouring achieves extremely high burst supersaturated nucleation, preventing atoms from growing too fast. The process migration arrangement is instantly frozen in the disordered framework, and nucleation occurs through a confined coprecipitation reaction for 20-40 minutes. After the reaction, the system is immediately sealed and placed in a sealed static aging environment of 0-5℃ for 2-6 hours. With the strong shear field of 700-900 rpm and sealed aging at 0-5℃, a homogeneous phase environment is locked and the spontaneous decomposition of weak base is inhibited. This confines the crystal nuclei at the nanoscale and inhibits Oswald ripening and agglomeration, stabilizes the homogeneous phase environment and inhibits the non-spontaneous ripening of the crystal nuclei. The amorphous primary product is obtained by solid-liquid separation.
[0042] S2. The amorphous initial product is introduced into 50°C water and eluted without stirring for 5-10 minutes using cavitation shear force with 100-200W ultrasound to forcibly extract and remove sterically hindered molecules deep in the pores. After washing and centrifuging once with 50°C water, once with room temperature water, and once with anhydrous ethanol, a wet gel solid is obtained. The wet gel solid is placed in a sealed static aging process at 0-5°C for 2-6 hours. A 100-200W ultrasound thermal elution process is used to forcibly break the self-assembled aggregates of high molecular weight surfactants deep in the pores using cavitation shear force, solving the problem of coking and carbonization caused by residues, and achieving high purification and exposure of active sites. The final stage introduces low surface tension ethanol for replacement and, combined with sealed aging at 0-5°C, effectively reduces the surface tension of the liquid phase and relaxes surface stress, preventing thermal collapse and pore compression of the metastable framework during the drying process, and ensuring the high specific surface area and long-range disorder characteristics of the catalyst. The aged wet solid product was transferred to a vacuum oven and dried at 55–65°C for 12–24 hours. This process provides gentle kinetic energy to slowly remove residual volatile solvents while minimizing phase separation during rapid evaporation of moisture, ensuring high chemical homogeneity of the copper, iron, and oxygen ternary components within the macroscopic amorphous solid framework. The precursor was then mechanically ground to obtain a pulverized product. This precursor was placed in a muffle furnace thermal shear field and heated to 250–400°C at a rate of 2–10°C / min in air. Precise control of the isothermal time (0.5–1.5 hours) achieved kinetic shearing of the microscopic phases, capturing the self-limiting crystal growth stage. The 0.5–1.5 hours heat treatment, while preserving the amorphous defect matrix, in-situ excited high-stress, locally distorted microcrystalline domains. This synergistic network of long-range disorder and locally ordered phases drove a rapid drop in the degradation curve, yielding an amorphous-crystalline bimetallic catalyst.
[0043] Example 1 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst, specifically including the following steps: S1. Dissolve 1.012 g of ferric nitrate nonahydrate, 0.6052 g of copper nitrate trihydrate, and 0.019 g of sodium hypophosphite monohydrate in 100 mL of ultrapure water and stir magnetically until completely dissolved to obtain a homogeneous salt solution. Add 0.030 g of dodecyl dimethyl ammonium bromide to the salt solution to obtain a mixed solution. Under mechanical stirring at 800 rpm, add 0.237 g of ammonium bicarbonate in one go to adjust the pH to 8.5 and carry out a coprecipitation reaction for 30 min. After the reaction is completed, immediately seal the system and place it in a completely physically sealed static aging environment at 5 °C for 2 h to stabilize the homogeneous phase environment and inhibit the non-spontaneous ripening of crystal nuclei. After solid-liquid separation, obtain the amorphous primary product.
[0044] S2. The amorphous precursor was introduced into 50°C ultrapure water and eluted without stirring for 5 min using cavitation shearing force with 100W ultrasound to forcibly extract and remove sterically hindered molecules deep within the pores. After washing and centrifuging once with 50°C ultrapure water, once with room temperature pure water, and once with anhydrous ethanol, a wet gel solid was obtained. This solid was immediately placed in a physically sealed static environment at 2°C for 6 h to relax surface stress and prevent the thermal collapse of the metastable framework. The aged wet solid product was transferred to a vacuum oven and dried at 60°C for 24 h. After mechanical grinding, the precursor was obtained. The precursor was placed in a muffle furnace thermal shear field and heated to 300°C at a programmed rate of 5°C / min in air atmosphere. By precisely controlling the isothermal time to 1 h, the kinetic shearing of the micro-phase was achieved, intercepting the self-limiting growth stage of the crystal, and an amorphous-crystalline bimetallic catalyst was prepared. After cooling, it was ground for later use and named a / c-CuFeP-1h.
[0045] Example 2 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that the isothermal time in S2 is replaced by 0.5 h instead of 1 h, and an amorphous-crystalline bimetallic catalyst is obtained, named a / c-CuFeP-0.5h.
[0046] Example 3 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that the isothermal time in S2 is replaced by 1.5h, and the amorphous-crystalline bimetallic catalyst is obtained and named a / c-CuFeP-1.5h.
[0047] Example 4 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that in S1, 0.019g of sodium hypophosphite monohydrate is replaced with 0.0095g to obtain an amorphous-crystalline bimetallic catalyst, named a / c-CuFeP-0.5P.
[0048] Example 5 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that the temperature in S2 is changed from 300℃ to 250℃, and the amorphous-crystalline bimetallic catalyst is obtained and named a / c-CuFeP-250.
[0049] Example 6 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that the temperature in S2 is changed from 300℃ to 400℃, and the amorphous-crystalline bimetallic catalyst is obtained and named a / c-CuFeP-400.
[0050] Example 7 This embodiment provides a method for preparing an amorphous-crystalline bimetallic catalyst. The difference between this embodiment and Example 1 is that in S1, the molar ratio of iron to copper in ferric nitrate nonahydrate and copper nitrate trihydrate is replaced from 1:1 to 1:3 to obtain an amorphous-crystalline bimetallic catalyst named a / c-CuFeP-1h(1:3).
[0051] Comparative Example 1 This comparative example provides a method for preparing a crystalline bimetallic catalyst. The difference between this comparative example and Example 1 is that the isothermal time in S2 is replaced by 4 hours instead of 1 hour, and a crystalline bimetallic catalyst is obtained, named c-CuFeP-4h.
[0052] Comparative Example 2 This comparative example provides a method for preparing an amorphous bimetallic catalyst. The difference between this comparative example and Example 1 is that no calcination was performed in S2, and its precursor is an amorphous bimetallic catalyst named a-CuFeP-0h.
[0053] Comparative Example 3 This comparative example provides a method for preparing a bimetallic catalyst. The difference between this comparative example and Example 1 is that sodium hypophosphite monohydrate was not added in S1, and the bimetallic catalyst was prepared and named c-CuFe-1h.
[0054] Comparative Example 4 This comparative example provides a method for preparing a metal catalyst. The difference between this comparative example and Example 1 is that no iron salt was added in S1, and the resulting metal catalyst was named a / c-CuP-1h.
[0055] Comparative Example 5 This comparative example provides a method for preparing a metal catalyst. The difference between this comparative example and Example 1 is that no copper salt was added in S1, and the resulting metal catalyst was named a / c-FeP-1h.
[0056] Experimental Example The metal catalysts prepared in Examples 1-7 and Comparative Examples 1-5 were characterized as follows: according to Figure 1It can be seen that the surface and interior of the amorphous-crystalline bimetallic catalyst prepared in Example 1 are composed of a three-dimensional porous network structure (sponge-like / coral-like) formed by the highly cross-linked and stacked nature of countless spherical nanoparticles.
[0057] according to Figure 2 It can be seen that the amorphous-crystalline bimetallic catalyst undergoes a complete phase evolution process from disorder to order. The precursor a-CuFeP-0h, prepared without calcination, exhibits only broad and gentle amorphous diffuse peaks in the 20°-40° region, confirming its completely long-range disordered state. Extending the calcination time to 4h yields c-CuFeP-4h, where the amorphous substrate completely disappears and transforms into sharp and intense crystalline diffraction peaks, indicating a long-range ordered rearrangement of atoms. Example 1, in an intermediate calcination time state, yields a / c-CuFeP-1h. While retaining the amorphous diffuse substrate, it begins to faintly precipitate weak crystalline diffraction peaks, strongly demonstrating that the "time shearing" strategy successfully blocked crystallization at the thermodynamic critical watershed of crystallization, constructing in situ a unique biphase structure where a long-range disordered amorphous substrate and localized microcrystalline domains coexist.
[0058] The metal catalysts prepared in Examples 1-7 and Comparative Examples 1-5 were subjected to performance tests, as detailed below: Using tetracycline as the target pollutant, the degradation effects of the metal catalysts prepared in Examples 1-7 and Comparative Examples 1-5 on tetracycline were tested. The specific procedures are as follows: (1) Prepare a tetracycline aqueous solution with a concentration of 20 mg / L, denoted as C0; divide it into multiple portions, each with a volume of 50 mL, as water samples for testing.
[0059] (2) Accurately weigh 7.5 mg of the metal catalyst powder prepared in Examples 1-7 and Comparative Examples 1-5 respectively, and add them to 50 mL of water samples for testing (addition amount is 0.15 g / L). Use ultrasound to fully disperse the metal catalyst to obtain each treatment sample.
[0060] (3) Place each treatment sample on a multi-stage stirring table and adjust the speed to 350 rpm for stirring. At this time, the mixture is in an intrinsically catalytically active state, and no additional external medium is required for the entire process.
[0061] (4) Add potassium persulfate (PMS) to each stirring system at one time to make its initial concentration 0.2 mmol / L, and immediately start the timer to carry out the catalytic degradation reaction at 25°C.
[0062] (5) At min 0, 2, 5, 10, 20, and 30 of the reaction, accurately extract 1.0 mL of the mixture, quickly filter it through a 0.22 μm filter membrane, and add 0.1 mL of anhydrous ethanol to the filtrate to terminate the reaction. The concentration C of residual tetracycline in the filtrate is determined using a UV spectrophotometer, and the residual rate at different time points is calculated to plot a curve showing its change over time. Figure 3-5 As shown.
[0063] according to Figure 3 It can be seen that the amorphous-crystalline bimetallic catalyst (a / c-CuFeP-1h) exhibits the best global catalytic activity. It shows explosive degradation (concentration drops sharply to about 35%) in the first 5 minutes of the reaction and achieves almost complete elimination of pollutants in 30 minutes. The overall degradation rate and removal efficiency significantly exceed those of amorphous a-CuFeP-0h and fully crystalline c-CuFeP-4h, which strongly confirms that the amorphous-crystalline bimetallic catalyst prepared in this example has a significant phase synergistic effect in the catalytic reaction due to the cross-linking structure of amorphous and crystalline biphases.
[0064] according to Figure 4 It can be seen that the amorphous-crystalline bimetallic catalysts prepared in Examples 1-7 showed obvious crossover between the curves at 2 min and 5 min due to the slight difference in their initial reaction rates (for example, some samples degraded relatively slowly at 2 min, but quickly caught up and surpassed at 5 min); while in the middle and later stages of the reaction, from 10 to 20 min, the residual concentration of pollutants (C / CO) had dropped to the low range of 0.05 to 0.25.
[0065] according to Figure 5 It can be seen that the curves of a / c-CuFeP-1h prepared in Example 1 were significantly lower than those of the metal catalysts prepared in Comparative Examples 1-5 throughout the entire reaction period, indicating that the catalytic effect of the amorphous-crystalline bimetallic catalyst prepared in Example 1 was significantly higher than that of Comparative Examples 1-5. At the 5 min and 10 min points of the reaction, the C / CO of Example 1 had dropped to 0.35 and 0.16, respectively, while the C / CO of the metal catalysts prepared in Comparative Examples 1-5 were concentrated in the high range of 0.60~0.80 and 0.40~0.60 at these two time points, respectively. At the end of the reaction period of 30 min, the C / CO of Example 1 was close to 0, while the residual concentration of the metal catalysts prepared in Comparative Examples 1-5 was between 0.12 and 0.25, and the curves showed obvious crossover and overlap with the data points in the latter half of the 20~30 min period.
[0066] At the microstructure level, this invention modulates the phase transition dynamics of heterogeneous catalytic materials through spatial control of multidimensional structures. Controlled characterization of a / c-CuFeP-0.5h and a / c-CuFeP-0.5P reveals that time shearing and the introduction of trace amounts of non-metallic heteroatoms near the critical watershed generate long-range topological resistance, thereby achieving synergistic coexistence of long-range disordered defect matrix and locally disordered distorted microcrystalline domains within both spatial and temporal upper limits. This structure not only avoids the decrease in active site density caused by long-term thermally driven (c-CuFeP-4h) atomic long-range ordered rearrangement and lattice self-repair, but also... The unique bimetallic multivalent state cyclic system (as opposed to the monometallic groups a / c-CuP-1h and a / c-FeP-1h) intertwines with the Fermi level mismatch between the disordered substrate and the nonmetallic P atom heterogeneous radius topological interference (as opposed to c-CuFe-1h), inducing a local charge polarization electric field at the nanoscale, reducing the influence of the intrinsic self-limiting resistance of the pure amorphous material (a-CuFeP-0h) surface, and constructing a multivalent state synergistic fast electron internal circulation network.
[0067] At the macroscopic application level, the charge orbital rearrangement and band topological shearing at the microscopic interface directly map to changes in the tetracycline interface scavenging behavior in multiphase advanced oxidation reactions. The benchmark group a / c-CuFeP-1h activated permonosulfate (PMS) with an amorphous / crystalline synergistic network exhibits specific scavenging kinetics. Its C / C0 value drops to 0.3477 after only 5 min of reaction, and it achieves basic removal (C / C0=0.0102) within 30 min. The degradation curve shifts significantly towards the low concentration quadrant. From the thermodynamic and kinetic perspective of the reaction, thanks to the complementary advantages of the amorphous high-density active site repository and the excellent conductivity and porous morphology of the microcrystalline domains, this catalyst can spontaneously drive the interfacial radical / non-radical evolution pathway in the intrinsic reaction system, without any additional cumbersome external equilibrium medium enhancement steps. This system integration, from microscopic phase interception to macroscopic low chemical loss catalysis, not only expands a new research perspective for the precise construction of metastable homogeneous-heterogeneous interfaces under atmospheric pressure isothermal kinetic shear, but also provides a useful reference for the structural design of advanced oxidation catalysts through this precise control of the phase transition window.
[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. The application of an amorphous-crystalline bimetallic catalyst in the catalytic degradation of organic pollutants in water, characterized in that, The preparation method of the amorphous-crystalline bimetallic catalyst includes the following steps: S1. Iron salt, copper salt and hypophosphite are dissolved in water and a surfactant is added to obtain a mixture; a weak alkali is added to the mixture under stirring, the pH is adjusted and a co-precipitation reaction is carried out. After the reaction is completed, the mixture is sealed and aged, and solid-liquid separation is performed to obtain an amorphous primary product. S2. The amorphous primary product is ultrasonically eluted, centrifuged, sealed and aged, and vacuum dried to obtain a precursor; the precursor is calcined at 250~400℃ for 0.5~1.5h to obtain an amorphous-crystalline bimetallic catalyst.
2. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, Iron salts include at least one of ferric chloride, ferric sulfate, ferric nitrate, or ferrous ammonium sulfate.
3. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, Copper salts include at least one of copper chloride, copper sulfate, copper nitrate, or copper acetate.
4. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, The molar ratio of iron to copper in iron and copper salts is 1:1 to 3; the molar ratio of the sum of iron and copper in iron and copper salts to phosphorus in hypophosphite is 20 to 100:
1.
5. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, The surfactant includes at least one of bis(dodecyl dimethyl)ammonium bromide, hexadecyl trimethylammonium bromide, or sodium dodecylbenzenesulfonate.
6. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, The weak alkaline agent includes at least one of ammonium bicarbonate, sodium bicarbonate or urea, with a pH of 7.5 to 9.
5.
7. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, The vacuum drying temperature is 55~65℃, and the time is 12~24h.
8. The application of the amorphous-crystalline bimetallic catalyst according to claim 1 in the catalytic degradation of organic pollutants in water, characterized in that, An amorphous-crystalline bimetallic catalyst is added to water, and persulfate is added as an oxidant to activate and degrade the organic pollutants.
